2007
DOI: 10.1300/j120v47n97_04
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging in an Academic Library: Integrating SMS into Digital Reference

Abstract: In spring 2005, Sims Memorial Library at Southeastern Louisiana University initiated "Text A Librarian," a service that enables Southeastern students, faculty, and staff to use the text message feature of their cell phones to send questions to and receive answers from the library. Librarians at Sims use a dedicated text messaging telephone number and "e-mail/SMS" conversion software, provided by Altarama Systems and Services, to send and receive text messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 2 publications
1
40
0
Order By: Relevance
“…These results are consistent with Hill, Hill, and Sherman (2007) findings, which suggested that students are willing to use mobile phone technologies to communicate with their instructor, and Kennedy et al's (2008) study which identified that students wanted to incorporate social tools such as instant messaging and texting into their academic studies. Given the high student comfort level with mobile phones and instant messaging, it is not surprising that students are willing to use these technologies in the academic setting.…”
Section: Comfort Levelsupporting
confidence: 87%
See 3 more Smart Citations
“…These results are consistent with Hill, Hill, and Sherman (2007) findings, which suggested that students are willing to use mobile phone technologies to communicate with their instructor, and Kennedy et al's (2008) study which identified that students wanted to incorporate social tools such as instant messaging and texting into their academic studies. Given the high student comfort level with mobile phones and instant messaging, it is not surprising that students are willing to use these technologies in the academic setting.…”
Section: Comfort Levelsupporting
confidence: 87%
“…Holley and Dobson (2008) added that students also bond; text messaging morphed groups that had been formed originally for academic purposes into longer lasting ''friendship groups. '' There is some evidence to suggest that students are willing to use text and instant messages for academic purposes including communicating with their tutors (Hill, Hill, and Sherman 2007) and asking questions on field placement (Young et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hill et al mention that the majority of questions are of the short-answer variety and relate to the library or the university; Giles and Grey-Smith report that the majority of questions require a simple explanation and can be answered in one text message; Kohl and Keating state that most questions are academic or ready reference questions and there are intermittent joke questions too; Wiemer finds that circulation questions, ready reference questions and database access questions are the three types of question that rank highest in number; Stahr summarizes that 86 percent of the questions are library reference questions with varying complexity, splitting between regular reference questions and questions concerning different aspects of library services such as library hours, circulation, behavior complaints, database, and remote access; Cole and Krkoska discover that about half of the questions are quick questions that only need a brief factual answer, and another half are substantive questions related to course assignments, research, or resources. 13 So far there has been one published study dedicated to the analysis of text reference transactions. In this study, Pearce et al focus on a number of transactional variables.…”
Section: Text Reference Servicementioning
confidence: 99%